An NO donor approach to neuroprotective and procognitive estrogen therapy overcomes loss of NO synthase function and potentially thrombotic risk. - Lawren VandeVrede (Public Library of Science (PLoS), 2013)
Selective estrogen receptor modulators (SERMs) are effective therapeutics that preserve favorable actions of estrogens on bone and act as antiestrogens in breast tissue, decreasing the risk of vertebral fractures and breast cancer, but their potential in neuroprotective and procognitive therapy is limited by: 1) an increased lifetime risk of thrombotic events; and 2) an attenuated response to estrogens with age, sometimes linked to endothelial nitric oxide synthase (eNOS) dysfunction. Herein, three 3(rd) generation SERMs with similar high affinity for estrogen receptors (ERα, ERβ) were studied: desmethylarzoxifene (DMA), FDMA, and a novel NO-donating SERM (NO-DMA). Neuroprotection was studied in primary rat neurons exposed to oxygen glucose deprivation; reversal of cholinergic cognitive deficit was studied in mice in a behavioral model of memory; long term potentiation (LTP), underlying cognition, was measured in hippocampal slices from older 3×Tg Alzheimer's transgenic mice; vasodilation was measured in rat aortic strips; and anticoagulant activity was compared. Pharmacologic blockade of GPR30 and NOS; denudation of endothelium; measurement of NO; and genetic knockout of eNOS were used to probe mechanism. Comparison of the three chemical probes indicates key roles for GPR30 and eNOS in mediating therapeutic activity. Procognitive, vasodilator and anticoagulant activities of DMA were found to be eNOS dependent, while neuroprotection and restoration of LTP were both shown to be dependent upon GPR30, a G-protein coupled receptor mediating estrogenic function. Finally, the observation that an NO-SERM shows enhanced vasodilation and anticoagulant activity, while retaining the positive attributes of SERMs even in the presence of NOS dysfunction, indicates a potential therapeutic approach without the increased risk of thrombotic events.